WİLLİAM MONTGOMERY WATT VE İLK DEVİR İSLAM TARİHİNE TARİHSELCİ BAKIŞ - Hasan Hüseyin Adalıoğlu (İslami İlimler Dergisi)
The views put forward by Western orientalists with regard to some aspects of early Islamic history have been taken seriously in the Islamic world and gave rise to numerous rejections by the Islamists. What made William Montgomery Watt different from the preceding orientalists is that he introduced relatively different approaches to the religious identity of the prophet and the current theories and arguements about the economic, social and political organization of Islam. The major characteristic of the theory developed by William Montgomery Watt is that he maintained his belief in Christianity and adopted a historicist approach to Islamic history while he at the same time accepted the religious identity of the prophet Muhammed (Peace be upon Him) and declared that he had seen the message of the prophet as a mere revelation from God. Indeed he has not considered the prophet only as a figure reacting under the influence of religious and external cultural factors, just to the contrary, he saw Him as a person reacting against social environment. Thus, Watt tried to analyze the social structure of Mecca of the time sociologically and physicologically and attempted to account for the political teachings of the prophet, which were fit for the social structure of his environment, from the perspective of an historicist. In spite of the fact that he is a priest, Watt today abstains from an overall decline although perhaps he does not have a genuine belief in Islam. This attitude of Watt, however, has attracted the criticism of various orientalists. With his new vision, Watt perhaps should be regarded as the pioneer of a new orientalist school or jeneration.